Somatic mutations and immune checkpoint biomarkers. Issue 3 (12th January 2019) - Parris, Brielle A.; Shaw, Eloise; Pang, Brendan; Soong, Richie; Fong, Kwun; Soo, Ross A.
ABSTRACT: The development of molecular testing for identifying somatic mutations and immune checkpoint biomarkers has directed treatment towards personalized medicine for patients with non‐small cell lung cancer. The choice of molecular testing in a clinical setting is influenced by cost, expertise in the technology, instrumentation setup and sample type availability. The molecular techniques described in this review include immunohistochemistry (IHC), fluorescent in situ hybridization, direct sequencing, real‐time polymerase chain reaction (PCR), denaturing high‐performance liquid chromatography, matrix‐assisted laser desorption/ionization time of flight mass spectrometry and next‐generation sequencing (NGS). IHC is routinely used in clinical practice for the classification, differentiation, histology and identification of targetable alterations of epidermal growth factor receptor ( EGFR ), anaplastic lymphoma kinase ( ALK ) and programmed death ligand‐1 (PD‐L1). Recently, the PD‐L1 pathway was identified as being exploited by tumour cells, allowing immune resistance and tumour evasion. The development of immune checkpoint inhibitors as treatment for tumours expressing checkpoints has highlighted the need for standardized IHC assays to inform treatment decisions for patients. Direct sequencing was historically the gold standard for mutation testing for EGFR, KRAS (Kirsten rat sarcoma viral oncogene homologue) and BRAF (v‐Raf murine sarcoma viral oncogene homologue B1) requiring a high ratio of tumour to normal cells, but this has been superseded by more sensitive methods. NGS is a new emerging technique, which allows high‐throughput coverage of frequently mutated genes, including less common BRAF and MET mutations and alterations in tumour suppressor genes. When an NGS platform is unavailable, PCR‐based technologies offer an efficient and cost‐effective single gene test to guide patient treatment. This article will review these techniques and discuss the future of molecular platforms underpinning clinical management decisions. Abstract : Cover Images : A NSCLC tissue section with no evidence of ALK gene rearrangement detectable using a break‐apart FISH probe design (LEFT; fused red and green signal within white circles), and a NSCLC tissue section with an ALK gene rearrangement illustrated within white ellipses by detached red and green signals tiling the 3' and 5' ends or isolated 3' red signals from the exon 20 breakpoint in the ALK gene (RIGHT).